2012
DOI: 10.1186/1029-242x-2012-121
|View full text |Cite
|
Sign up to set email alerts
|

L p Bounds for the parabolic singular integral operator

Abstract: Let 1 < p <∞ and n ≥ 2. The authors establish the L p (ℝ n+1 ) boundedness for a class of parabolic singular integral operators with rough kernels. MR(2000) Subject Classification: 42B20; 42B25.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Precisely, they proved that is bounded for any 1 under the condition that . Recently, a considerable amount of research has been done to obtain the boundedness of the operator , the readers are refereed (for instance to [3] , [4] and the references therein).…”
Section: Preliminaries and Statement Of Resultsmentioning
confidence: 99%
“…Precisely, they proved that is bounded for any 1 under the condition that . Recently, a considerable amount of research has been done to obtain the boundedness of the operator , the readers are refereed (for instance to [3] , [4] and the references therein).…”
Section: Preliminaries and Statement Of Resultsmentioning
confidence: 99%
“…Recently, Chen, Ding and Fan [10] extended further the condition to the case ∈ H 1 S n−1 . Moreover, it follows from Chen, Wang and Yu's work [11] that T is bounded on L p (R n ) for 2β/(2β − 1) < p < 2β provided that ∈ F β S n−1 for some β > 1, where…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Chen, Ding and Fan extended further the condition to the case ΩH1Sn1. Moreover, it follows from Chen, Wang and Yu's work that T is bounded on Lp(Rn) for 2β/(2β1)<p<2β provided that ΩscriptFβSn1 for some β>1, where scriptFβSn1:=ΩL1()Sn1:0.16emsupξSn1Sn1|Ω(y)|prefixlog1|ξ·y|βdσ(y)<,β>0.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Chen, Ding, and Fan [3] extended further the condition to the case: normalΩH1(Sn1)$\Omega \in H^1(S^{n-1})$, where H1(Sn1)$H^1(S^{n-1})$ denotes the Hardy space defined on Sn1$S^{n-1}$. Moreover, it follows from Chen, Wang, and Yu's work [4] that TnormalΩ$T_{\Omega }$ is bounded on Lp(double-struckRn)$L^p(\mathbb {R}^n)$ for 2β/false(2β1false)<p<2β$2\beta /(2\beta -1)&lt;p&lt;2\beta$ provided that normalΩFβ(Sn1)$\Omega \in \mathcal {F}_{\beta }(S^{n-1})$ for some β>1$\beta &gt;1$. Here, Fβ(Sn1)$\mathcal {F}_{\beta }(S^{n-1})$ denotes the set of all Ω, which are integrable over Sn1$S^{n-1}$ and satisfies supξSn1Sn1|Ωfalse(yfalse)…”
Section: Introductionmentioning
confidence: 99%
“…\end{equation*}$$This class of functions was introduced by Grafakos and Stefanov [9] and it was showed that Fβ2(Sn1)Fβ1(Sn1),1em0.16em0.16em1goodbreak<β1goodbreak<β2,$$\begin{equation*} \mathcal {F}_{\beta _2}{\big(S^{n-1}\big)}\subsetneqq \mathcal {F}_{\beta _1}{\big(S^{n-1}\big)},\quad \forall \,\, 1&lt;\beta _1&lt;\beta _2, \end{equation*}$$β>1Fβ(Sn1)H1(Sn1)βbadbreak>1Fβ(Sn1),$$\begin{equation*} \bigcap \limits _{\beta &gt;1}\mathcal {F}_{{\beta }}{\big(S^{n-1}\big)}\nsubseteq H^1{\big(S^{n-1}\big)}\nsubseteq \bigcup \limits _{\beta &gt;1} \mathcal {F}_{\beta }{\big(S^{n-1}\big)}, \end{equation*}$$and qbadbreak>1Lq(Sn1)Fβ(Sn1),1em0.222222em0.16emβgoodbreak>1.$$\begin{equation*} \bigcup \limits _{q&gt;1}L^q{\big(S^{n-1}\big)}\subsetneqq \mathcal {F}_{\beta }{\big(S^{n-1}\big)},\quad \forall \:\,\beta &gt;1. \end{equation*}$$Very recently, the authors in [11] further generalized the result of [4] to the mixed radial‐angular spaces Lρfalse(xfalse)pLθp…”
Section: Introductionmentioning
confidence: 99%